KOMBINASI PEMBERIAN ARANG HAYATI DAN CUKA KAYU TERHADAP PERTUMBUHAN JABON DAN SENGON - Sri Komarayati; Gustan Pari (Jurnal Penelitian Hasil Hutan, 2014)
Biocharcoal is a specific charcoal that can store carbon in soil almost permanently, and be able to improve its humidity aswell as fertility. This paper observes the use of biocharcoal and wood vinegar to stimulate jabon and sengon seedlings.Biochar and wood vinegar were made of sawdust, charcoal, compost charcoal (a mixture of sawdust charcoal and compost)and wood vinegar (the condensed gas/vapor fractions that evolved during sawdust carbonization). Sawdust and compostcharcoals were mixed thoroughly and evenly with the top soil for jabon and sengons media. Wood vinegar in 2%concentration was then poured and sprayed onto the planted seedlings. Similar seedlings were also planted on the untreatedsoil media as a control. After five months seedlings growth characteristics (i.e. height and diameter) were observed andmeasured. Results show that in general, height and diameter of the seedlings planted in treated media are improved.Seedlings of Jabon are increased by 16.38 , 21.05 , and 62.74 times in height as well as 1.70 and 3.10 times in diameterthan those of control. Seedlings of Sengon are increased by 22.50, 21.10, 40.80 times in height as well as and 1.04 and1.03 in diameter than those of control.